Faktor-Faktor yang Berhubungan dengan Praktik Antenatal Care pada Remaja dengan Kehamilan Tidak Diinginkan (Study di Wilayah UPT Puskesmas Ponjong 1 Kabupaten Gunungkidul) - Endah Nur Wakhidah; Kusyogo Cahyo; Ratih Indraswari (Jurnal Kesehatan Masyarakat (Undip), 2017)
A good Antenatal Care (ANC) is needed by teenagers with unwanted pregnancy to keep the mother and baby healthy and to prevent complication on pregnancy, giving birth, and antenatal period. Data from SDKI in 2012 showed that 10% of teenagers already became mothers. The amount of giving birth cases in DIY on 2015 is 1078, with Gunungkidul Regency being the first, i.e.: 405 cases. On the year of 2014, unwanted pregnancy in Gunungkidul was 188 cases;on 2015, it has been increased to be 158 cases. In UPT Puskesmas Ponjong I, 38% of teenagers experience unwanted pregnancy. On 2015, unwanted pregnancy cases in teenagers are increased to be 52%, i.e.: 24 from 46 pregnancies of teenagers. The aim of this research is to know the related factors of ANC practice in teenagers with unwanted pregnancy. This research is a qualitative research using cross sectional approach. The technique used is total sampling technique, i.e.: 43 teenagers with unwanted pregnancy on 2014 and 2015 in UPT Puskesmas Ponjong I. The collecting data is done by using interview and questionnaire methods. Data analysis is done by univariate and bivariate. All of respondents are on the category of end teenagers (15 – 19 years old);most of them are 17 years old (39,5%) and graduated from Junior High School (79,1%). From the data, it is found that most of respondents have good knowledge about ANC (74,4%), have attitude of supporting ANC practice (76,7%), do ANC adequately (76,7%), less of cultural values support ANC practice (27,9%); then,  less of respondents are not reached the ANC access (41,9%), not reached on ANC cost (48,8%); most of official competencies are good (74,4%) most of respondents get support from the husbands/couple (74,4%), get support from parents (53,5%), and get support from their peers (60,5%). Related variable to the ANC practice is knowledge of ANC (p=0,043). Variables which not related to the ANC practice are attitude to ANC (p=0,362), cultural value (p=11), access affordability (p=0,067), cost affordability (p=0,162), official competencies (p=1,000), support from husbands/couple (p=1,000), support from parents (p=0,728), support from peers (p=0,269).